2003
DOI: 10.1116/1.1585064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NH3 thermal treatment on an atomic layer deposited on tungsten films and formation of W–B–N

Abstract: The effect of ammonia (NH 3 ) ambient annealing on a tungsten ͑W͒ film deposited by atomic layer deposition at temperatures ranging from 400-700°C is discussed. The as-deposited film contains approximately 20 at. % of boron which is chemical bound to W ͑W-B͒ having a resistivity of 128 ⍀ cm. The film has an amorphous structure, which does not transform into crystalline phase during annealing. As a result of annealing in NH 3 ambient, a tungsten ternary phase ͑W-B-N͒ forms at the surface; its binding configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…During postdeposition thermal treatment, nitrogen in the WN layer could easily be out-diffused 19,20) in regions where the B-N compound reaction could take place. 21,22) The change in Gibbs free energy 23) during the formation of B-N is as large as À225 kJ/mol, which is higher than that of Si-N (À216 kJ/mol). This stable insulative B-N interlayer could lead to an increase in gate R c .…”
Section: B-n Resistance Modelmentioning
confidence: 99%
“…During postdeposition thermal treatment, nitrogen in the WN layer could easily be out-diffused 19,20) in regions where the B-N compound reaction could take place. 21,22) The change in Gibbs free energy 23) during the formation of B-N is as large as À225 kJ/mol, which is higher than that of Si-N (À216 kJ/mol). This stable insulative B-N interlayer could lead to an increase in gate R c .…”
Section: B-n Resistance Modelmentioning
confidence: 99%
“…Compared to sputtered Ti-B-N coatings, little research work has been carried out on the W-B-N system. The few exploratory investigations [5][6][7][8] showed that this ternary system is an excellent diffusion barrier, due to a dense amorphous structure, relatively high crystallisation temperature and chemical inertness.…”
Section: Introductionmentioning
confidence: 99%